Ambiente de aprendizagem híbrido no Ensino de Química: uma perspectiva de inovação pedagógica na era da aprendizagem móvel - Silva, Eliete Braga (2018)
The current scenario of classrooms, through the advancement of mobile devices, and the growing expansion of connectivity options, is faced with students moving through social networks or seeking information with “Mr. Google.” This implies an analysis and evaluation in the teaching process in order to adapt it to the current moment. In addition, it is necessary to reflect and evaluate the potential of Digital Information and Communication Technologies (TDIC) in the educational process. In education persists, a misconception about these devices, especially in the public network. It is common to find some technological equipment in the so-called “Computer Laboratories”. However, these are available, usually outdated and are not sufficient to meet the number of students per class. In addition to the lack of computers, copiers for xeroxcopies are expensive, and schools do not receive money for maintenance, limiting the use of complementary materials. This makes the textbook the only source for applying exercises, making it difficult to recognize the student’s abilities and competences inside and outside the school environment. However, schools can not isolate themselves, we must overcome these conditions of backwardness, and get close to what the new generations are living. As a space of exchange and interaction of the educational process, it becomes feasible to add values to the use of mobile devices in a productive way, aiming to aid the teaching process. In addition, it is fundamental to integrate the TDIC in situations and experiences beyond the walls of the school. It is necessary to arouse students’ interest in having pleasure in knowing, in learning to think and in elaborating the information so that it can be applied to the reality they are living. Through this posture, the school approaches the students, satisfying the need for frequent connection that they have, of being connected to the device with such frequency. In this context, the guiding problem of this research emerges: How to constitute a hybrid learning environment using smartphones in the process of teaching and learning Chemistry in a public school system? From this problem, it was tried to evaluate if the TDIC modifies the relation that is established inside and outside the classroom, between teachers and students. And it can act as a support for students to become protagonists acting with more autonomy in their learning. Participants of the survey were 240 high school students from the public network. Questionnaires, customized activities, debates, interviews were instruments of data production, analyzed qualitatively. The results showed that participants have broad access to smartphones and the internet, but their use was basically restricted to social networks. Initially, the use of the virtual environment caused the participants a bit of anguish because they perceived some fragility in the domain of the configurations of their device. However, they have been adapting and concluding that they need to be open to the new paradigms that communicate from an increasingly broad and technological universe. As such, it was possible to integrate Google Classroom as an online environment, organized for a hybrid learning, available to any technological device, especially smartphones, enabling the activities inside and outside the classroom.